An examination of major works for wind band: “Hands across the sea march” by John Philip Sousa, “Michigan's motors” by Thomas Duffy, “In the forest of the king: a suite of old French songs' by Pierre la Plante and “Yorkshire ballad” by James Barnes. - Bailey, Candace Leann (Kansas State University, 2010)
The following report details the research and analysis required for completion of the degree, Master of Music from Kansas State University. This project was culminated in the conducting performance by Candace Bailey of four pieces during the 2009-2010 school year. The symphonic, concert and combined bands of Shawnee Mission North High School in Overland Park, KS contributed time, skills and feedback for the successful performance of Hands Across the Sea by John Philip Sousa, Michigan’s Motors by Thomas Duffy, Yorkshire Ballad by James Barnes and In the Forest of the King by Pierre LaPlante. Documentation of processes are detailed in lesson plans and critical evaluations of rehearsals. Analysis models were provided by the Unit Teacher Resource Guide, developed by Richard Miles, and the Macro-Micro-Macro score analysis form created by Dr. Frank Tracz.
Keywords: Music; Band; Music (0413)